Budd Chiari syndrome due to segment VIII hepatic hydatidosis treated by cystectomy with good evolution: First national observation - Delgado, Bolívar; Perrier, José P; Risi, Leonardo (Cirugía del Uruguay, 1991)
The authors present a case of Budd-Chiari syndrome caused by a calcified hydatic cyst in the Vlllth hepatic segment which was surgically treated by cystectomy with satisfactory evolution. This is the first national observation with these characteristics.